Predictive and prognostic significance of sodium levels in patients with NSCLC treated by erlotinib - Svaton, Martin; Fiala, Ondrej; Pesek, Milos; Bruha, Frantisek; Mukensnabl, Petr; Racek, Jaroslav; Minarik, Marek; Bortlicek, Zdenek (Anticancer research, 2014)
BACKGROUND: Hyponatremia is a well-known phenomenon in cancer patients. The aim of our retrospective study was to assess the relationship of natremia levels to predict treatment with erlotinib and also to assess the prognosis of patients with hyponatremia. PATIENTS AND METODS: We analyzed data of 544 patients with advanced-stage non-small cell lung cancer (NSCLC) treated with erlotinib. RESULTS: Hyponatremia was measured in 21.5 % of patients before treatment with erlotinib. We found a significant increase in the effectiveness of treatment with erlotinib in patients with normal levels of sodium to hyponatremic patients. Progression-free survival (PFS) and overall survival (OS) were also significantly higher in patients with normal natremia. Multivariate Cox model analysis demonstrated that natremia was an independent factor for PFS and OS. CONSLUSION: We reported hyponatremia not only as a prognostic marker in NSCLC patients but also as predictive marker of erlotinib treatment efficacy, being an independent factor at the present large retrospective study. Its possible effect in clinical practice is bigger thanks the simple possibility of testing of hyponatremia and the low cost of this biomarker.
Keywords: výsledek terapie; proporcionální rizikové modely; Disease-Free Survival; Male; retrospektivní studie; nádory plic; NSCLC; Carcinoma, Non-Small-Cell Lung; Lung Neoplasms; Erlotinib Hydrochloride; erlotinib; Proportional Hazards Models; Adult; Aged; dospělí; sodík; mužské pohlaví; senioři; inhibitory proteinkinas; Treatment Outcome; Sodium; senioři nad 80 let; prognosis; hyponatremie; OS; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; nemalobuněčný karcinom plic; Hyponatremia; Protein Kinase Inhibitors; erbB receptory; Aged, 80 and over; PFS; Quinazolines; Retrospective Studies; predictive marker; chinazoliny; Female; ErbB Receptors; lidé středního věku; nádorové biomarkery; přežití bez známek nemoci; Middle Aged